Left ventricular geometry and diastolic function in the hypertensive heart: Impact of age. (February 2013) - Negri, Francesca; Sala, Carla; Re, Annalisa; Mancia, Giuseppe; Cuspidi, Cesare
Abstract Background and aim. The impact of aging on the relationship between left ventricular (LV) mass/geometry and diastolic function as assessed by updated echocardiographic methods, such as tissue Doppler, is poorly defined. We investigated this issue in a cohort of hypertensive patients. Methods. A total of 660 hypertensives (mean age 65 ± 13 years, 48% men) with preserved LV systolic function underwent a comprehensive echo-Doppler examination for routine clinical indications. For the present analysis, the subjects have been divided in two age groups (<65 or ≥65 years). Results. Overall, 61% of subjects fulfilled the criteria for LVH, 18% for left atrial (LA) enlargement and 11% for altered LV filling index. Concentric LV geometry was 1.4-fold higher in older hypertensives than in younger counterparts; also the prevalence of LA enlargement and altered LV filling was 2.0- and 1.9-fold higher in the former group, respectively. In older hypertensives, at variance from younger ones, neither LV mass nor relative wall thickness (RWT), a continuous index of LV geometry, were independently correlated to conventional as well as tissue Doppler LV diastolic indexes. Conclusions. Our findings suggest the relationship between cardiac hypertrophy and diastolic function in hypertensive subjects is affected by aging-associated factors unrelated to the amount of LV mass as assessed by standard echocardiography.